Directed Reading Thinking Activity (DRTA) Strategy on Students’ Reading Comprehension of Narrative Text - Ayu Lutfiah Dewi; Ainol Ainol; Achmad Kholili (Universitas Pendidikan Mandalika, 2023)
DRTA is a reading comprehension strategy for students, especially narrative texts. Balajthy (2003) in his book says Russell Stauffer in 1975 developed the directed reading thinking activity (DRTA) as a more attractive alternative to the course outline model used in most basic guided reading courses. The DRTA strategy was advanced to encourage active reading comprehension and move the student to assume critically to understand the text. The design of a quasi-experimental with a design non-equivalent control class was employed since this investigates the efficacy of using the DRTA strategy for improving students’ reading comprehension of the narrative text. The observation, test, and documentation were collected in this study. The question test consisted of 20 items using pretest-posttest, in the VIIIA class, which included 22 female students were used as an experimental class, and the VIIIB class, which included 14 male students was used as the control class. An independent sample t-test was used to analyze the evidence to find out whether the DRTA strategy improved the students’ reading comprehension. The result showed that the T-test value was 4,698 with probably Sig two-sided 0,001, the score Sig two-sided 0,001 < 0,05. The experimental class that received the DRTA strategy differs significantly from the control class that did not receive treatment. As a result, it will draw a conclusion that the DRTA strategy is effective for the education and studying of the activity of eight grade students at the MTS Miftahul Jannah.